Тараканище: стихи / К. Чуковский ; худож.: В. А. Жигарев, В. Л. Вахтин - Чуковский Корней Иванович (Фламинго, 2015)
Экземпляры: ДО мл.аб. (2021) / Инвентарный номер: 56719 / Цена: 8.50. / Сис.шифр: 84(2Рос=Рус)-5 / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2РОс=Рус)6